2020
DOI: 10.3390/su12052034
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Effects of the Built Environment on Two Transfer Modes for Metros: Dockless Bike Sharing and Taxis

Abstract: The success of metro systems depends on effective multimodal solutions that bridge the first-and-last-mile gaps. Both dockless bike sharing (DBS) and taxis are important feeder modes for metros, which provide on-demand travel options with high flexibility and accessibility. Based on one-week trip data of DBS and taxis during a concurrent period in Beijing, China, the paper aims to compare the temporal-spatial distribution of two modes as first-and-last-mile connectors and find out the socio-demographic and bui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 57 publications
2
36
0
Order By: Relevance
“…As for the built environment, mixed land use, parks and public squares, and transportation facilities such as bicycle lanes have been found to be positively related to integrated use (Guo and He 2020). Areas that are less economically developed with fewer signalized intersections are more favored by those who use metro-bicycle integration (Ni and Chen 2020). However, research conclusions have differed among cities.…”
Section: Literature Review: Factors Involved In Cyclingmentioning
confidence: 99%
See 2 more Smart Citations
“…As for the built environment, mixed land use, parks and public squares, and transportation facilities such as bicycle lanes have been found to be positively related to integrated use (Guo and He 2020). Areas that are less economically developed with fewer signalized intersections are more favored by those who use metro-bicycle integration (Ni and Chen 2020). However, research conclusions have differed among cities.…”
Section: Literature Review: Factors Involved In Cyclingmentioning
confidence: 99%
“…The public bicycle is widely believed to be one of new ways to solve the last-mile problem (Liu et al 2012;Ma et al 2015;Ni and Chen 2020). It can improve the accessibility to public transportation systems by directly connecting the origin/destination and metro stations (Liu et al 2012;Zhang et al 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bicycle turnover and time-varying demand characteristics varied widely across docked public bicycle stations, with bicycle stations adjacent to public transportation stations, shopping centers, restaurants, schools, and finance having high ridership on both weekdays and weekends, but stations adjacent to office concentration areas having high ridership only on weekdays [39]. Dockless bike-sharing usually serves the initial or last mile of public transportation transfer connections, and suburban areas with dense branch roads and few traffic light intersections are more popular among bike-sharing users [40]. Population density and employment density are the two most significant factors affecting bike-sharing use, and built environment has a nonlinear effect on bike-sharing use [41].…”
Section: Literature Reviewmentioning
confidence: 99%
“…To what extent findings from docked bike-sharing studies on mode substitution apply to dockless bike-sharing remains unexplored. In addition, although increasing evidence has revealed that individuals' socio-demographics, attitudes, and built environment often influence how, when, and where dockless bike-sharing systems are used (e.g., Guo & He, 2020;Ni & Chen, 2020), there is a lack of knowledge about how these factors relate to the mode that is substituted for. Finally, it is unclear what role varying travel purposes, such as commuting or traveling for leisure, play in mode substitution patterns of dockless bike-sharing.…”
mentioning
confidence: 99%